Differentiate the function y = (x^2)/(3x-1) with respect to x.

This requires use of the quotient rule: d/dx[f(x)/g(x)] = [g(x)f'(x) - g'(x)f(x)]/[g(x)^2]dy/dx = ([(3x-1)*2x] - 3x^2)/[(3x-1)^2],= (3x^2-2x)/[(3x-1)^2],=[x(3x-2)]/[(3x-1)^2]

Answered by Ted S. Maths tutor

5829 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve x^2=3(x-1)^2


By using partial fractions, integrate the function: f(x) = (4-2x)/(2x+1)(x+1)(x+3)


How do you integrate (2x)/(1+x^2) with respect to x?


How do you 'rationalise the denominator'?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences